2020
DOI: 10.1016/j.ctrv.2020.102019
|View full text |Cite
|
Sign up to set email alerts
|

Review of precision cancer medicine: Evolution of the treatment paradigm

Abstract: In recent years, biotechnological breakthroughs have led to identification of complex and unique biologic features associated with carcinogenesis. Tumor and cell-free DNA profiling, immune markers, and proteomic and RNA analyses are used to identify these characteristics for optimization of anticancer therapy in individual patients. Consequently, clinical trials have evolved, shifting from tumor type-centered to gene-directed, histology-agnostic, with innovative adaptive design tailored to biomarker profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
312
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(316 citation statements)
references
References 123 publications
2
312
0
2
Order By: Relevance
“…[40,48] Recent studies suggest that genomic selection of patients for clinical trials can be a useful approach for treatment. [77][78][79][80][81][82][83][84] In the case of malignancies harboring aberrant BAP1, directly targeting BAP1 functions using HDAC inhibitors and EZH2 inhibitors, as well as targeting DNA damage repair mechanisms with the use of platinums or PARP inhibitors may be a viable approach. Additionally, augmenting the immune response via checkpoint blockade and/or other modalities of immunotherapy are strategies that merit further investigation.…”
Section: Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…[40,48] Recent studies suggest that genomic selection of patients for clinical trials can be a useful approach for treatment. [77][78][79][80][81][82][83][84] In the case of malignancies harboring aberrant BAP1, directly targeting BAP1 functions using HDAC inhibitors and EZH2 inhibitors, as well as targeting DNA damage repair mechanisms with the use of platinums or PARP inhibitors may be a viable approach. Additionally, augmenting the immune response via checkpoint blockade and/or other modalities of immunotherapy are strategies that merit further investigation.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Recent studies suggest that personalized combination therapies may be a more optimal approach, particularly for molecularly complex tumors. [78,83] Given that BAP1 is involved in a number of biological pathways and interacts with an array of cancer-associated genes, this type of combinatorial approach may be necessary. One strategy may be to binds to ASXL to form the PR-DUB complex, responsible for regulation of chromatin through Histone H2A deubiquitination.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Precision oncology, a strive for personalized medicine that targets unique molecular aberrations in patients, has made tremendous progress in the last decade in various cancers, 7 but is lagging far behind in MPM. 8 Comprehensive genomic studies have shown a rarity of oncogenic driver mutations in MPM, 9,10 while inactivating mutations [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is the 4th leading cause of cancer-related deaths worldwide and it consists of almost 90% pancreatic cancers (1,2). Although in recent years significant improvements have been achieved in the diagnosis and treatment of different kinds of cancers (3), the mortality rate of PDAC has not experienced substantial changes during the past decades. This is because PDAC is a highly destructive cancer with an extraordinarily high malignancy and a particularly poor prognosis (4).…”
Section: Introductionmentioning
confidence: 99%